Conservation genomics reveals pesticide and pathogen exposure in the declining bumble bee Bombus terricola. Issue 17 (11th July 2021) - Tsvetkov, Nadejda; MacPhail, Victoria J.; Colla, Sheila R.; Zayed, Amro
Abstract: In recent years, many pollinators have experienced large population declines, which threaten food security and the stability of natural ecosystems. Bumble bees are particularly important because their ability to "buzz" pollinate and tolerate cooler conditions make them critical pollinators for certain plants and regions. Here, we apply a conservation genomics approach to study the vulnerable Bombus terricola . We sequenced RNA from 30 worker abdomens, 18 of which were collected from agricultural sites and 12 of which were collected from nonagricultural sites. We found transcriptional signatures associated with exposure to insecticides, with gene expression patterns suggesting that bumble bees were exposed to neonicotinoids and/or fipronil—two compounds known to negatively impact bees. We also found transcriptional signatures associated with pathogen infections. In addition to the transcriptomic analysis, we carried out a metatranscriptomic analysis and detected five pathogens in the abdomens of workers, three of which are common in managed honey bee and bumble bee colonies. Our conservation genomics study provides functional support for the role of pesticides and pathogen spillover in the decline of B . terricola . We demonstrate that conservation genomics is an invaluable tool which allows researchers to quantify the effects of multiple stressors that impact pollinator populations in the wild.